OS X Mavericks on demand. - Johnson, Steve, 1961- (Que Pub., 2013)
Need answers quickly? OS X Mavericks on Demand provides those answers in a visual step-by-step format. We will show you exactly what to do through lots of full color illustrations and easy-to-follow instructions. Inside the Book Find and preview everything you need with Spotlight Master the OS X Mavericks user interface and file management Use the App Store and full-screen apps for maximum efficiency Explore the Internet with Safari and send e-mail with Mail Manage and play digital music with iTunes and iPhone, iPad, or iPod Chat online instantly with Messages and FaceTime Manage and share your schedule with Calendar Send files wirelessly to anyone around you with AirDrop Keep your files synced to iCloud and backed up with Time Machine Automatically save document changes as you work with Auto Save Use multi-touch gestures and keyboard shortcuts to save time Post content straight to Facebook, Twitter, Flickr, or Vimeo Use Microsoft Windows along with Mavericks Numbered Steps guide you through each task See Also points you to related information in the book Did You Know? alerts you to tips and techniques Illustrations with matching steps Tasks are presented on one or two pages Bonus Online Content Register your book at queondemand.com to gain access to: Workshops and related files Keyboard shortcuts Visit the author site: perspection.com.